Appendiceal intussusception with chronic abdominal pain (Bangladesh Journal of Medical Science, 2026)
Appendiceal intussusception is a rare condition due to partial/total invagination of the appendix into the colon. A 26-year-old woman, with no underlying comorbidities, complained of right lower colicky abdominal pain for the last 8 months. She denied fever, diarrhoea, per-rectal bleeding or significant weight loss. Clinically, the right iliac fossa and suprapubic tenderness were noted with positive rebound tenderness. Ultrasonography of the abdomen revealed invagination of the appendix to the caecum, suggesting appendiceal intussusception. Open appendectomy was performed after failure of reduction through laparoscopic approach. It is important to have a high degree of suspicion to make the diagnosis, especially among young women with chronic abdominal pain.BJMS, Vol. 25 No. 01 January’26 Page : 360-363